1987
DOI: 10.3109/17453678709146459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the calcaneofibular ligament on hindfoot rotation in amputation specimens

Abstract: A kinesiologic study of the range of rotation in the hindfoot after cutting of the calcaneofibular ligament was performed in amputation specimens. Cutting of. the calcaneofibular ligament results in a significant increment in the external rotation of the tibial-talocalcaneal joint complex and the talocalcaneal joint, maximum 5.4" and 2.9", respectively. The total range of rotation in the tibial-talocalcaneal joint complex and the talocalcaneal joint increased 32 and 20 per cent, respectively. The calcaneofibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 13 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…Damage to both of these ligaments results in an increase of varus tilting of the talus within the ankle mortise [25,27]. The calcaneofibular ligament is rarely injured alone, but with or without a combined lesion of the anterior fibular ligament, rupture of this ligament is reported to result in an increase of motion in the subtalar joint [2,10,16,18,20,26,30,32,33,35]. Increase in talocalcaneal movement is found when a lesion of the calcaneofibular ligament is combined with a lesion of the interosseous talocalcaneal ligament [13].…”
Section: Introductionmentioning
confidence: 97%
“…Damage to both of these ligaments results in an increase of varus tilting of the talus within the ankle mortise [25,27]. The calcaneofibular ligament is rarely injured alone, but with or without a combined lesion of the anterior fibular ligament, rupture of this ligament is reported to result in an increase of motion in the subtalar joint [2,10,16,18,20,26,30,32,33,35]. Increase in talocalcaneal movement is found when a lesion of the calcaneofibular ligament is combined with a lesion of the interosseous talocalcaneal ligament [13].…”
Section: Introductionmentioning
confidence: 97%
“…Kjärsgard‐Andersen et al . [10,11] found the CFL to be an important structure in the rotatory stabilization of the hindfoot. Finally, accompanying injury to the medial collateral ligaments of the ankle may also result in persistent rotational instability of the ankle.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason may be the presence of subtalar joint instability, resulting from combined injury to both the anterior talo®bular ligament (ATFL) and calcaneo®bular ligament (CFL). Kja Èrsgard-Andersen et al [10,11] found the CFL to be an important structure in the rotatory stabilization of the hindfoot. Finally, accompanying injury to the medial collateral ligaments of the ankle may also result in persistent rotational instability of the ankle.…”
Section: Introductionmentioning
confidence: 99%
“…Since Rubin and Witten34 for the first time suggested the clinical significance of subtalar instability, this topic has received a considerable amount of attention.5,9,15. [22][23][24]27,42,[44][45][46][47][48][49] Clanton" concludes that subtalar instability must be considered as a cause of symptoms in a patient who sustains an inversion type of injury to the ankle and hindfoot, particularly if other causes of instability have been excluded.…”
Section: Introductionmentioning
confidence: 99%